Development of Teaching Materials Drama for Web-Based to Improve the Students’ Skill for Digital Literacy and English Language for Students at FKIP UMSU - Ratna Sari Dewi; Diani Syahputri (Budapest International Research and Critics University, 2020)
The purpose of this research is to develop instructional materials web-based for drama subject who is feasible and valid at Teacher Training and Education Department (FKIP) at Muhammadiyah University of Sumatera Utara and effectively to improve the students’ achievement in Digital Literacy as well as English Language. The research and development model used 4 D (Define, Design, Develop and Disseminate). The instrument of this research is questionnaires given to the seventh grade students. To test the quality of instructional drama material and tested the validity and practicality assessed by experts (material and media experts), lecturers and students. To find out the students ability in term of digital literacy and English language, the students given the tests. This research is analyzed by using Linkert Scale. The findings of the research are developed at umsu’s website that is e-learning.umsu.com. The result of experiment to experts, lecturers and students showed that instructional web based for drama subject is feasible and valid, besides it is also effective to improve the students’ achievement in digital literacy and English language.